Limit-Point/Limit-Circle Results for Superlinear Damped Equations - M. Bartušek; John R. Graef (Abstract and Applied Analysis)
The authors study the nonlinear limit-point and limit-circle properties for second-order nonlinear damped differential equations of the form (a(t)|y'|p-1y')'+b(t)|y'|q-1y'+r(t)|y|λ-1y=0, where 0<q≤p≤λ, a(t)>0, and r(t)>0. Examples to illustrate the main results are included.